Differences in motor variability among individuals performing a standardized short-cycle manual task - Sandlund, J.; Srinivasan, D.; Heiden, M.; Mathiassen, Svend (Elsevier BV; North Holland, 2017)
ï¿½ 2016 Elsevier B.V. Motor variability (MV) has been suggested to be a determinant of the risk for developing musculoskeletal disorders in repetitive work. In this study we examined whether individuals consistently differed in the extent of motor variability when performing a standardized short-cycle manual task. On three separate days, arm kinematics was recorded in 14 healthy subjects performing a pipetting task, transferring liquid from a pick-up tube to eight target tubes with a cycle time of 2.8ï¿½s. Cycle-to-cycle standard deviations (SD) of a large selection of shoulder and elbow kinematic variables, were processed using principal component analysis (PCA). Thereafter, between-subjects and between-days (within-subject) variance components were calculated using a random effects model for each of four extracted principal components. The results showed that MV differed consistently between subjects (95% confidence intervals of the between-subjects variances did not include zero) and that subjects differed consistently in MV between days. Thus, our results support the notion that MV may be a consistent personal trait, even though further research is needed to verify whether individuals rank consistently in MV even across tasks. If so, MV may be a candidate determinant of the risk of developing fatigue and musculoskeletal disorders in repetitive occupational work.